Influence of morphological characteristics on physical and physiological performances of Tunisian elite male handball players - Moncef, C.; Said, M.; Olfa, N.; Dagbaji, G. (Asian Journal of Sports Medicine, 2012)
Purpose: The purpose of this study was to describe the body structure and morphological characteristics of Tunisian elite handball players, and to determine the effect of these variables on functional and physical performance levels.